SISTEM INFORMASI EDUKASI PENANGANAN HUTAN LINDUNG DAERAH KONSERVASI BANTIMURUNG DI KABUPATEN MAROS - sirwan; Nasir, Khaidir; Disa, Syaharullah; Sumardin, A; Kamal, Kamal (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
Conservation Areas are environmental assets that are very important for maintaining biodiversity and ecosystems. Maros Regency, as one of the regions that has the Bantimurung Protected Forest Area, has challenges in preserving this forest. This research aims (1) to design an educational information system for handling protected forests in the Bantimurung conservation area; (2) To implement a website-based educational information system for handling protected forests in the Bantimurung conservation area. The research method used is the waterfall model development (R & D) method with stages of analysis, design, coding and testing. The research results show that (1) the Bantimurung Conservation Area Education Information System, Maros Regency, was designed as an educational medium for the community to increase accessibility and understanding about maintaining ecosystems in conservation areas in Maros Regency. This system was successfully built using the PHP programming language, MySQL. (2) Test results based on UAT from 22 respondents who tested the system show that 90% of the system is suitable for use.